Analysis of Quality Control of Shrimp Crop Products with Seven Tools and FMEA Methods (Case Study : UD. Djaya Bersama) - Novan Andi Ansyah; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2022)
In this modern era, customers are more concerned with the quality of goods offered by manufacturers. Therefore, the company maintains the quality and feasibility of the products produced to ensure customer satisfaction. Analysis of the quality of the production process at UD. DJAYA BERSAMA is rarely done. This resulted in many defective products that escaped and were then returned to the company. This research was conducted at UD. DJAYA BERSAMA in order to control the quality of shrimp cracker products using the seven tools and FMEA methods. This method is often chosen because it has been used by previous researchers and has proven to be effective as a tool for data processing and factor analysis of the production process in order to improve product quality and make a decision. This study uses a qualitative descriptive analysis method collected by seven tools. This data collection is done in several ways. Primary data was obtained through observation, interviews with employees and production staff, while secondary data was obtained from related literature. From the results of research that has been carried out using the seven tools and FMEA methods, the level of product defects is still stable because there is no control chart that exceeds UCL and LCL. And the highest RPN value is on molen mace with an RPN value of 120.